Генеральный округ Волынь и Подолия в материалах белорусских архивов - Гребень, Евгений; Hreben, Y. (Волинський національний університет імені Лесі Українки, 2012)
В статье характеризуются документы периода нацистской оккупации, относящиеся к генеральному округу Волынь и Подолия, хранящиеся в настоящее время на территории Республики Беларусь. Дается аннотация фондов государственного архива Брестской области, анализируются различные группы архивных документов, относящихся к белорусским территориям, входившим в состав генерального округа Волынь и Подолия. Documents of the period of Nazi occupation relating to the General District of Volhynia and Podolia are characterized in the article. They are currently stored on the territory of the Republic of Belarus. The summary of funds of the State Archives of Brest Region is given, different groups of archival documents relating to the Belarusian territories that formed the part of the General District of Volhynia and Podolia are analyzed.
The General District of Volhynia and Podolia in the Materials of Belarusian Archives
Keywords: нацистская оккупация; рейхскомиссариат Украина; генеральный округ Волынь и Подолия; Брестский; Пинский; Столинский округа; Nazi occupation; Reichskommissariat Ukraine; General District of Volhynia and Podolia; Brest; Pinsk; and Stolin districts